C-Reactive Protein dan D-Dimer sebagai Prediktor Mortalitas Pasien COVID-19 - Raynaldo E. D. Togas; Mordekhai L. Laihad; Diana C. Lalenoh (Universitas Sam Ratulangi, 2023)
Abstract: High mortality rate of COVID-19 patients is caused by cytokine storms which worsen the condition of COVID-19 patients, so that COVID-19 infection is associated with an inflammatory and prothrombotic state. C-reactive protein (CRP), which is a marker of inflammation, and also D-dimer, which is a marker of coagulation, have increased in relation to the severity of COVID-19 disease. This study aimed to determine whether inflammatory markers (CRP) and coagulation profiles (D-dimer) could be used as predictors of mortality in COVID-19 patients. This was a literature review study by searching three databases, namely Pubmed, Sciencedirect, and Google Scholar. The results obtained 11 literatures with a total sample of 6,440 COVID-19 patients with CRP and/or D-dimer marker test results. Six of seven literatures showed significant results that increased CRP level was a predictor of mortality in COVID-19 patients, and six of the six literatures showed significant results that increased D-dimer level was a predictor of mortality in COVID-19 patients. In conclusion, CRP and D-dimer can be used as predictors of mortality in COVID-19 patients Keywords: COVID-19; C-reactive protein; D-dimer; predictor of mortality; cytokine storms Abstrak: Tingginya angka mortalitas pasien COVID-19 disebabkan oleh badai sitokin yang meningkatkan perburukan kondisi pasien COVID-19 sehingga infeksi COVID-19 dikaitkan dengan keadaan inflamasi dan protrombotik. C-reactive protein (CRP) yang merupakan penanda inflamasi dan juga D-dimer yang merupakan penanda koagulasi mengalami peningkatan terkait dengan derajat beratnya penyakit COVID-19. Penelitian ini bertujuan untuk mengetahui apakah penanda inflamasi (CRP) dan profil koagulasi (D-dimer) dapat digunakan sebagai prediktor mortalitas pasien COVID-19. Metode penelitian ialah suatu literature review dengan pencarian menggunakan tiga database, yaitu Pubmed, Sciencedirect, dan Google Scholar. Hasil penelitian mendapatkan 11 literatur dengan jumlah sampel penelitian 6440 pasien COVID-19 serta hasil tes penanda CRP dan atau D-dimer. Enam dari tujuh literatur memiliki hasil bermakna bahwa peningkatan kadar CRP sebagai prediktor mortalitas pasien COVID-19, dan enam dari enam literatur memiliki hasil bermakna bahwa peningkatan kadar D-dimer sebagai prediktor mortalitas pasien COVID-19. Simpulan penelitian ini ialah CRP dan D-dimer dapat digunakan sebagai prediktor mortalitas pasein COVID-19. Kata kunci: COVID-19; C-reactive protein; D-dimer; prediktor mortalitas; badai sitokin